1998
DOI: 10.1128/jvi.72.3.2500-2504.1998
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus (HIV) Envelope Binds to CXCR4 Independently of CD4, and Binding Can Be Enhanced by Interaction with Soluble CD4 or by HIV Envelope Deglycosylation

Abstract: Chemokine receptor CXCR4 (also known as LESTR and fusin) has been shown to function as a coreceptor for T-cell-tropic strains of human immunodeficiency virus type 1 (HIV-1). We have developed a binding assay to show that HIV envelope (Env) can interact with CXCR4 independently of CD4 but that this binding is markedly enhanced by the previous interaction of Env with soluble CD4. We also show that nonglycosylated HIV-1SF-2 gp120 or sodium metaperiodate-treated oligomeric gp160 from HIV-1451 bound much more readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(30 citation statements)
references
References 32 publications
0
27
0
3
Order By: Relevance
“…Several other studies demonstrated that prebinding soluble forms of Tva to ALV(A) virions produced activated viruses capable of infecting Tva-negative cells (10,17,60). Viral envelope preactivation has also been proposed for the observed enhancement of infection of CD4-negative cells by some HIV and simian immunodeficiency virus variants preadsorbed with soluble CD4 (6,57). A variety of selective forces, including development of resistance to viral entry by the host, are probably responsible for retroviruses evolving to use different receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies demonstrated that prebinding soluble forms of Tva to ALV(A) virions produced activated viruses capable of infecting Tva-negative cells (10,17,60). Viral envelope preactivation has also been proposed for the observed enhancement of infection of CD4-negative cells by some HIV and simian immunodeficiency virus variants preadsorbed with soluble CD4 (6,57). A variety of selective forces, including development of resistance to viral entry by the host, are probably responsible for retroviruses evolving to use different receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These include proteolytic processing, protein folding, and glycosylation. Glycosylation of the hemagglutinin of influenza A and envelope of lentiviruses can have dramatic effects on cleavage activation, immune escape, virulence, and interactions with cellular receptors (3,6,7,12,13,16,27,47,53,55,56,76). In contrast to the ample information regarding effects of glycosylation on virus attachment proteins is the limited knowledge of the effects of receptor glycosylation on virus-receptor interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of small-molecule antagonists of CXCR4 and readily selected strains of HIV-1 that can resist inhibitor challenges highlights the flexibility of Env and the need to understand the interaction of ligands with CXCR4 to design more effective antiretroviral agents (20,21,38,46,49,56). Recent advances in detecting direct Env interactions with CCR5 have enhanced our understanding of the role of the chemokine receptors in fusion (37,41,52,61,67,68), but direct interactions of X4 Envs with CXCR4 have been difficult to study (4,34,39,43).…”
mentioning
confidence: 99%